2020
DOI: 10.3390/cells9010145
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Aggregation in Intrinsically Disordered Proteins Is Determined by Charge and Lipophilicity

Abstract: Protein aggregation is associated with an increasing number of human disorders and premature aging. Moreover, it is a central concern in the manufacturing of recombinant proteins for biotechnological and therapeutic applications. Nevertheless, the unique architecture of protein aggregates is also exploited by nature for functional purposes, from bacteria to humans. The relevance of this process in health and disease has boosted the interest in understanding and controlling aggregation, with the concomitant dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 71 publications
4
38
0
Order By: Relevance
“…At the same time, IDPs are extremely sensitive to environmental conditions; an effect often disregarded in predictive approaches. Among the different parameters that may affect IDPs' properties, the solution pH has a significant impact, mainly due to the high prevalence of ionizable residues in these polypeptides [14,15,17,29]. In this work, we demonstrated that the effect of pH on the disordered nature of a protein sequence could be easily predicted by evaluating the changes in protein charge and hydrophobicity as a function of this parameter.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…At the same time, IDPs are extremely sensitive to environmental conditions; an effect often disregarded in predictive approaches. Among the different parameters that may affect IDPs' properties, the solution pH has a significant impact, mainly due to the high prevalence of ionizable residues in these polypeptides [14,15,17,29]. In this work, we demonstrated that the effect of pH on the disordered nature of a protein sequence could be easily predicted by evaluating the changes in protein charge and hydrophobicity as a function of this parameter.…”
Section: Discussionmentioning
confidence: 84%
“…In recent work, we showed that the solution's pH effect on IDPs solubility is not restricted to its effect on the charge of ionizable residues since the pH also modulates the sequence hydrophobicity [17], a traditionally neglected effect. Driven by this simple idea, we revisit here the C-H concept, on the evidence that both protein net charge and hydrophobicity are dependent on pH.…”
Section: Introductionmentioning
confidence: 99%
“…Disordered regions have different properties according to composition, which might correspond to different properties and functions [ 16 ]. For example, their distributions of charged residues can affect their level of compaction [ 38 ], conformational preferences [ 39 ] and phosphorylation [ 40 ], which ultimately influence the propensity of IDPs to aggregate [ 41 , 42 , 43 ], interact with other proteins [ 44 ] and perform phase separation [ 45 ]. To complement our analysis of disorder emergence in orthologs presented above, we evaluated the presence of compositionally biased regions (CBRs) in these proteins (using CAST [ 25 ]).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it could be argued that high-NCPR proteins (i.e., polyelectrolytic IDPs) are much more sensitive than polyampholytes to even slight pH changes. Results from [ 83 ] have led to the development of an empirical equation suitable to predict pH-dependent aggregation of amyloidogenic IDPs and, hence, to promote the design of synthetic solubility/aggregation tags, as well as reversibly aggregating nanofibrillar materials [ 84 ].…”
Section: Relevance Of Electrostatic Charges In Protein Solubility/mentioning
confidence: 99%